Public Interest, Professional Bargains: Ethical Conflicts Between Lawyers and Professional Engineers - Elizabeth J. Hubertz (Washington University Journal of Law & Policy, 2009)
This Article analyzes the ethical obligations of interdisciplinary practice among environmental lawyers and engineers.
Keywords: Architecture – Law & amp; legislation; Lawyers; Conflicts of interest; Legal ethics; Environmental engineers